A theoretical framework of the drivers of CSR: The role of strategic planning and firm culture - Galbreath, Jeremy (Curtin University of Technology, 2007)
Corporate social responsibility (CSR) is argued to be a strategic imperative, one that can significantly affect firm competitiveness. However, little research demonstrates what actually shapes or drives firms towards proactive CSR. This paper proposes that strategic planning is one such driver in that it creates awareness of and formulates responses to a firm?s stakeholders, thereby enabling CSR. But while a strategic planning effort can develop the best and most impressive strategies ? those that drive CSR ? they might be actualized in a manner more or less than intended given the type of firm culture in place. Thus, firm culture is argued to moderate the relationship between strategic planning and CSR.